2013
DOI: 10.1039/c3fd00050h
|View full text |Cite
|
Sign up to set email alerts
|

Double layer effects at nanosized electrodes†

Abstract: This paper discusses numerical simulations of double layer effects at shrouded electrodes with dimensions below 100 nm. Special focus is given to the surface charge on the shrouding material. The Poisson-Nernst-Planck equations are solved to study the effects on the limiting current arising from the electrical double layer of the shrouding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a typical voltammetric measurement with excess supporting electrolyte (SE), λ D is typically ∼1 nm. Accordingly, ion migration effects resulting from the electric-field-driven ion transport are negligible at macroscopic electrodes, and diffusion is the dominant contribution to mass transport. At low ionic strength, however, a significant depletion zone forms, accompanied by a sizable electric field, and if two electrodes are sufficiently close that their EDLs overlap, ion migration can contribute significantly to mass transport and thus to faradaic currents. ,, As a result, currents can be enhanced or diminished depending on the charge of the redox-active species and whether the electrode reaction increases or decreases it. ,,, …”
mentioning
confidence: 99%
“…In a typical voltammetric measurement with excess supporting electrolyte (SE), λ D is typically ∼1 nm. Accordingly, ion migration effects resulting from the electric-field-driven ion transport are negligible at macroscopic electrodes, and diffusion is the dominant contribution to mass transport. At low ionic strength, however, a significant depletion zone forms, accompanied by a sizable electric field, and if two electrodes are sufficiently close that their EDLs overlap, ion migration can contribute significantly to mass transport and thus to faradaic currents. ,, As a result, currents can be enhanced or diminished depending on the charge of the redox-active species and whether the electrode reaction increases or decreases it. ,,, …”
mentioning
confidence: 99%
“…However, eq is valid for conditions where diffusion dominates, and electromigration contributes negligibly to mass transport, since the measurements are performed in the presence of a large concentration of supporting electrolyte (SE) . In contrast, at low ionic strength, ion migration can contribute significantly to mass transport. This effect occurs because the Debye length, λ D , depends on ionic strength, so at low ionic strength the electric field extends from the electrode surface into the bulk of solution, which can either promote or impede the movement of ions to the electrode surface. The enrichment of Ru(NH 3 ) 6 3+/2+ in the negatively charged nanopores to maintain electroneutrality, a phenomenon that has been widely observed in nanopores and nanofluidic channels at low ionic strength, could also contribute to the observed current amplification. Enhanced currents have been observed at low ionic strength on a single microelectrode, producing a several-fold increase in I lim for the reduction of cationic species or oxidation of anionic species in the absence of SE. , In this study, we explore how migration effects, in combination with ion enrichment at nanopore-confined electrodes, might be further exploited to enhance mass transport in a dual electrode system exhibiting the RC effect, resulting in additional current amplification. Migration effects are expected to be larger in dual electrode systems, since the electric field established across the two electrodes can drive the movement of ions, at least in one direction, speeding up the redox cycling events.…”
mentioning
confidence: 99%
“…Furthermore, they showed that the size of nanoparticles could be determined with sub-angstrom resolution by detecting the current drop across the orice. 114 As the diameter of a nanopore decreases to a few nanometers, approaching the thickness of the electrical double layer, eld driven migration [119][120][121][122][123] and eldinduced accumulation or depletion [124][125][126][127][128] of charged entities in the nanopores become important. By controlling the surface charge of nanopore electrodes, the accumulation of oppositely charged ions leads to an enhancement in the ionic current through the nanopore.…”
Section: Nanopores Nanochannels and Nanopipettesmentioning
confidence: 99%